The G6055A (G2019S) mutation in LRRK2 is frequent in both early and late onset Parkinson's disease and originates from a common ancestor. Issue 11 (4th November 2005) - Goldwurm, S; Fonzo, A Di; Simons, E J; Rohé, C F; Zini, M; Canesi, M; Tesei, S; Zecchinelli, A; Antonini, A; Mariani, C; Meucci, N; Sacilotto, G; et al.
Abstract : Background: Mutations in the gene Leucine-Rich Repeat Kinase 2 ( LRRK2 ) were recently identified as the cause of PARK8 linked autosomal dominant Parkinson's disease. Objective: To study recurrent LRRK2 mutations in a large sample of patients from Italy, including early (<50 years) and late onset familial and sporadic Parkinson's disease. Results: Among 629 probands, 13 (2.1%) were heterozygous carriers of the G2019S mutation. The mutation frequency was higher among familial (5.1%, 9/177) than among sporadic probands (0.9%, 4/452) (p<0.002), and highest among probands with one affected parent (8.7%, 6/69) (p<0.001). There was no difference in the frequency of the G2019S mutation in probands with early v late onset disease. Among 600 probands, one heterozygous R1441C but no R1441G or Y1699C mutations were detected. None of the four mutations was found in Italian controls. Haplotype analysis in families from five countries suggested that the G2019S mutation originated from a single ancient founder. The G2019S mutation was associated with the classical Parkinson's disease phenotype and a broad range of onset age (34 to 73 years). Conclusions: G2019S is the most common genetic determinant of Parkinson's disease identified so far. It is especially frequent among cases with familial Parkinson's disease of both early and late onset, but less common among sporadic cases. These findings have important implications for diagnosis and genetic counselling in Parkinson's disease.